Representaciones del arquetipo de Drácula en la novela “Guía del club de lectura para matar vampiros” de Grady Hendrix - Lema Caiza, Jessica Tatiana (2025)
The vampire is a mythical creature that has prevailed and fascinated humanity for centuries, establishing itself as an archetypal figure in Bram Stoker's novel Dracula. Over the years, the archetype has been reinterpreted in various ways in literature, film, theater, and other media. The objective of this research was to characterize the archetype of Dracula in Grady Hendrix's novel The Southern Book Club's Guide to Slaying Vampires, a 21st-century work of horror fiction. The study took a qualitative approach, using a basic, documentary-based bibliographic design. The main technique used was content analysis, therefore, the work focuses on the analysis and interpretation of two literary works, Dracula and The Southern Book Club's Guide to Slaying Vampires. It is concluded that the narrative of Dracula contributes to the formation of the archetype, with the novel focusing on mystery and horror surrounding this vampire. Furthermore, Dracula reflects the social anxieties, concerns, and fears of its time, the late 19th century. In comparing the two works, it was possible to see the influence of Stoker's classic on the other, as well as distinct vampire characteristics, capturing new ideas and new human fears, and different gender and power relationships in the characters. This suggests that the literary work Dracula paves the way for future modifications of the archetype.